(untitled) (Iranian Journal of Kidney Diseases, 2010)
Introduction. Helicobacter pylori infection in gastric mucosa may cause systemic inflammatory reaction. We investigated the inflammatory effect of H pylori infection on nutritional factors such as serum albumin in hemodialysis patients and influence of eradication of H pylori on this association. Materials and Methods. Ninety-eight patients on hemodialysis were divided into 2 groups according to H pylori infection. Eradication of H pylori, 8 weeks after treatment, was confirmed by urease breath test and H pylori stool antigen. Serum albumin, lipid profile, and metabolite levels were checked before and after 8 weeks and 6 months of eradication of H pylori. Results. Thirty-nine patients (39.8%) were infected with H pylori. There were no significant differences between the two groups in age, dialysis duration, serum albumin, serum creatinine, blood urea nitrogen, hemoglobin, serum calcium, serum phosphorus, and lipid profile. Thirty-seven patients with H pylori completed the treatment period. Eradication was successful in 30 patients (81.1%). Eight weeks and 6 months after anti-H pylori drug therapy, the mean serum albumin level significantly decreased from 4.2 mg/dL to 3.6 mg/dL (P < .001) and 3.7 mg/dL (P < .001), respectively. Significant decreases were seen in serum cholesterol (P = .001), blood urea nitrogen (P = .005), and serum calcium level (P = .03) and a significant increase in hemoglobin level (P = .02). Conclusions. Our study did not demonstrate nutritional benefits after H pylori eradication treatment, as the level of nutritional markers reduced. This relationship needs to be confirmed by further prospective studies.